Legal Analysis Of Cryptocurrency Asset Investments Under The Commodity Futures Trading Regulatory Framework In Indonesia - Dicky Widianto Pamungkas; Pujiyono Suwadi (Badan usaha Milik Desa Berkaho Pungpungan, 2026)
The landscape of cryptocurrency asset investments in Indonesia is currently challenged by regulatory uncertainty, conflicting directives among interrelated state institutions regarding digital assets, and weak protection against critical vulnerabilities such as the profound risk of malicious hacking. Addressing these core issues, this study evaluates the legal safeguarding and regulatory oversight of crypto asset investments within the Indonesian jurisdiction . Utilizing a normative juridical methodology based on a documentary study of primary, secondary, and tertiary legal materials, and analyzed qualitatively, the findings indicate that: Ministry of Trade Regulation No. 99 of 2018 regarding the General Policy for Crypto Asset Futures Trading, and Commodity Futures Trading Supervisory Agency (Bappebti) Regulation No. 5 of 2019 on Technical Provisions for the Physical Crypto Asset Market establish the primary legal foundation. Transactional validity in futures trading relies on Indonesian contract principles under the Burgerlijk Wetboek (BW) and its foundational doctrines. Furthermore, these digital transactions hold legality under Law No. 11 of 2008 concerning Electronic Information and Transactions (ITE Law) due to their digital execution. Consequently, investors acquire juridical protection against cybercrime-induced detriments and civil damages originating from Unlawful Acts (Perbuatan Melawan Hukum/PMH), specifically fraudulent practices (bedrog). Bappebti’s surveillance mechanism, governed by Regulation No. 5 of 2019, addresses physical market traders, asset criteria, and reporting standards. However, while aligning with operational protocols, Bappebti's regulatory framework exhibits deficiencies in effectively mitigating the aforementioned systemic and cyber risks.